Beware of the echo: the evolution of Egypt's population and labor force from 2000 to 2050. Issue 1 (2nd January 2022) - Assaad, Ragui
ABSTRACT: I argue in this paper that although recent developments had temporarily reduced demographic pressures on the Egyptian labor market, such pressures will return with a vengeance in the next decade. The sizable echo generation born between 2005 and 2015 is the reflection of the large youth bulge generation born in the early 1980s; a reflection that was further compounded by rising fertility rates in the late 2000s and early 2010s. As the echo generation reaches working age, the net annual increase to the labor force will rise from 575 thousand per year in 2020–25 to 800 thousand per year in 2030–35, which will pose a major job creation challenge. This upcoming wave of new entrants will also be substantially more educated, with 50–60 percent having secondary or post-secondary education, and another third having university education or higher. To accommodate this upcoming growth in labor supply and absorb the stock of existing unemployed and discouraged workers, I estimate that employment growth would have to reach 2.7 percent per year, something that would require sustained GDP growth rates in excess of 6 percent per year. The quality of jobs created by the Egyptian economy would also have to improve substantially to satisfy the higher aspirations of the increasingly educated new entrants and curtail the rising rates of discouragement among female new entrants.